Modelno podprt sistem za dinamično nastavljanje rezalnih parametrov pri postopku frezanja - Čuš, Franc (Strojniški vestnik, 2007)
This paper presents a model-based mechanism of control ensuring the constant quality of the surface finish by controlling the cutting forces during the end-milling process. Using the dynamic adaptation of feeding and speed the system controls the surface roughness and the cutting forces on the milling cutter. The purpose of developing such a mechanism is to find the limitations of this type of control, which maintains a constant cutting force by adapting the cutting parameters. This model-based system of control was developed by the evolutionary method of genetic programming (GP). A drawing of experiments was made in order to determine the empirical correlations between the quality of the surface finish and the cutting force. With the depth of cutting defined in advance the influence of the workpiece material and cutting parameters (feeding, cutting depth) on the above mentioned correlation has been experimentally researched. The evolution genetic programming method (GP) was applied to derive an empirical relationship for the surface finish and the cutting force values for steel materials. These relationships were applied to develop the proposed evolution simulation model in which the cutting force is adjusted to improve the required surface quality for the end-milling process. The results provide a means for greater efficiency by improving the surface quality, minimizing the effect of the process variability and reducing the error cost during finishing operations.
Keywords: frezanje; genetsko programiranje; sistemi vodenja